«Зелена кімната» як ефективна форма роботи з дітьми, що потерпіли від сексуального насильства - Малиновська, Т. М.; Malynovska, T. M.; ORCID: http://orcid.org/0000-0002-7713-7617 (Європейські перспективи. - 2021. - № 3. – С. 103-107, 2021)
Наголошено, що з метою приведення роботи поліцейських до міжнародних стандартів у сфері ювенальної юстиції та удосконалення системи досудового розслідування у справах за участю дітей виникла необхідність у забезпеченні єдиного підходу до допиту дітей з використанням методики «зелена кімната». Проаналізовано чинне кримінальне процесуальне законодавство в частині допиту постраждалих дітей. Акцентовано увагу на масштабність випадків сексуального насильства й іншої агресивної поведінки щодо дітей і на необхідність удосконалення процесуальних прогалин у чинному законодавстві.

Ensuring the best interests of a child as a priority principle for the formation and implementation of child-friendly justice is regulated both by international standards and legislation and regulatory legal acts of Ukraine. Ukraine as a member of the Council of Europe has committed to implement standards for the protection of children who are victims of violence or witnesses to crimes. The issue of reforms in the field of safety and protection of children’s rights, ensuring their best interests, introduction of innovative methods of preventive work is especially relevant and one of the leading areas of state policy. However, it should be noted that the legislative process does not meet public expectations in regard to a balanced and systematic reform of Ukrainian legislation. In order to bring the work of police officers to international standards in the field of juvenile justice and to improve the system of pre-trial investigation in cases involving children, there is a need to ensure the unified approach to the interrogation of children by using the “green room”. The purpose of the article is to analyze the current criminal procedural legislation in terms of interrogation of children who are victims; to emphasize the attention on the scale of cases of sexual abuse and other aggressive behavior against children and the need to improve procedural gaps in the current legislation.

Отмечено, что с целью приведения работы полицейских к международным стандартам в области ювенальной юстиции и усовершенствования системы досудебного расследования по делам детей, возникла необходимость в обеспечении единого подхода к допросу детей с использованием методики «зеленая комната». Проанализировано действующее уголовное процессуальное законодательство по допросу пострадавших детей. Акцентировано внимание на масштабности случаев сексуального насилия и другого агрессивного поведения в отношении детей и необходимости совершенствования процессуальных пробелов в действующем законодательстве.
«Green room» as an effective form of work with children who have been suffered from sexual abuse
Малиновська, Т. М. «Зелена кімната» як ефективна форма роботи з дітьми, що потерпіли від сексуального насильства / Малиновська Тетяна Миколаївна // Європейські перспективи. - 2021. - № 3. – С. 103-107. - DOI: 10.32782/EP.2021.3.15.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; сексуальне насильство; sexual violence; сексуальное насилие; допит дитини; interrogation of the child; допрос ребенка; "зелена кімната"; "green room"; "зеленая комната"; захист прав дитини; protection of children's rights; защита прав ребенка; кримінально-процесуальне законодавство; criminal procedural legislation; уголовно-процессуальное законодательство; допит дітей, що потерпіли від насильства